Development and Evaluation of Maze-Like Puzzle Games to Assess Cognitive and Motor Function in Aging and Neurodegenerative Diseases - Nef, Tobias; Chesham, Alvin; Schütz, Narayan; Botros, Angela Amira; Vanbellingen, Tim; Burgunder, Jean-Marc; Müllner, Julia; Martin Müri, René; Urwyler, Prabitha (Frontiers in Aging Neuroscience, 2020)
There is currently a need for engaging, user-friendly and repeatable tasks for assessment of cognitive and motor function in aging and neurodegenerative diseases. This study evaluated the feasibility of a maze-like Numberlink puzzle game in assessing differences in game-based measures of cognition and motor function due to age and neurodegenerative diseases. Fifty-five participants, including young (18 – 31 years, n=18), older (64 – 79 years, n=14) and oldest adults (86 – 98 years, n=14), and patients with Parkinson’s (59 – 76 years, n=4) and Huntington’s disease (35 – 66 years, n=5) played different difficulty levels of the Numberlink puzzle game and completed usability questionnaires and tests for psychomotor, attentional, visuospatial, and constructional and executive function. Analyses of Numberlink game-based cognitive (solving time and errors) and motor (mean velocity and movement direction changes) performance metrics revealed statistically significant differences between age groups and between patients with Huntington’s disease and older adults. However, patients with Parkinson’s disease did not differ from older adults. Correlational analyses showed significant associations between game-based performance and movement metrics and performance on neuropsychological tests for psychomotor, attentional, visuospatial, and constructional and executive function. Furthermore, varying characteristics of the Numberlink puzzle game succeeded in creating graded difficulty levels. Findings from this study support recent suggestions that data from a maze-like puzzle game provides potential ‘digital biomarkers’ to assess changes in psychomotor, visuoconstructional and executive function related to aging and neurodegeneration. Especially, game-based movement measures from the maze-like puzzle Numberlink games are promising as a tool to monitor the progression of motor impairment in neurodegenerative diseases. Further studies are needed to more comprehensively establish the cognitive validity and test-retest reliability of using Numberlink puzzles as a valid cognitive assessment tool.